2019
DOI: 10.1542/peds.2018-3532
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Workload of Pediatricians in China

Abstract: OBJECTIVES: Although it is widely believed that China is facing a major shortage of pediatricians, the real situation of the current national status of pediatric human resources and their working conditions has not been evaluated to date. METHODS: We administered a survey to 54 214 hospitals from all 31 provinces in mainland China from 2015 to 2016. Hospital directors of all secondary and tertiary hospitals with pediatric ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 24 publications
1
67
1
Order By: Relevance
“…According to the 2016 population census, the population of children aged 0-14 years is 1 million in China (http://www.stats.gov.cn/tjsj/ pcsj/rkpc/6rp/indexch.htm). A previous study revealed that there were 135,524 pediatricians in China and 4 pediatricians per 10,000 children; the pediatricians reported being very stressed and having a greater workload (Zhang et al, 2019). By March 29, 2020, 146 cases of COVID-19 were reported in patients between the age of 55 days old and 87 years old in Guizhou Province, and 2 patients died (http://www.gzhfpc.…”
mentioning
confidence: 99%
“…According to the 2016 population census, the population of children aged 0-14 years is 1 million in China (http://www.stats.gov.cn/tjsj/ pcsj/rkpc/6rp/indexch.htm). A previous study revealed that there were 135,524 pediatricians in China and 4 pediatricians per 10,000 children; the pediatricians reported being very stressed and having a greater workload (Zhang et al, 2019). By March 29, 2020, 146 cases of COVID-19 were reported in patients between the age of 55 days old and 87 years old in Guizhou Province, and 2 patients died (http://www.gzhfpc.…”
mentioning
confidence: 99%
“…FSS aims to improve parental involvement in education and parent–teacher collaboration in order to improve children's behavior and academic performance. However, there are currently only 135,524 pediatricians in China, just four per 10,000 children ( 20 ). Therefore, when we did the behavior management training, we simplified the course to make the training feasible and effective in China.…”
Section: Methodsmentioning
confidence: 99%
“…China's efforts to control the growth of costs are focused on eliminating markups in drug prices, reducing the price of drugs, and controlling the behavior of public hospitals. Public of pediatricians was 12.6% (14). According to another survey, 71.0% of physicians in China would not encourage their children to pursue a medical specialty (15).…”
Section: Financial Stressmentioning
confidence: 99%